PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP EFISIENSI OPERASIONAL DI SEKTOR PUBLIK - Zahwatun Suhaibah Rangkuti; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the impact of management information systems (MIS) on operational efficiency in the public sector. Utilizing a descriptive approach based on analyses from various previous journals, this research focuses on how MIS affects multiple operational aspects, such as data management, decision-making, and resource allocation in public institutions. The results indicate that the adoption of MIS significantly improves efficiency by reducing work duplication, enhancing inter- departmental communication, and streamlining administrative processes. MIS implementation also promotes greater transparency and accountability in daily operational activities. However, challenges such as dependency on technological infrastructure and employee resistance were identified as obstacles to MIS implementation. This study concludes that MIS has significant potential to enhance operational efficiency in the public sector when coupled with effective implementation strategies.